The Effect of Perceived Uncertainty on Purchase Intention of Blind Box Product: Curiostiy as Mediator and Perceived Risk as Moderator - Sitti Nabilah Annisa; Nur Afifah; Wenny Pebrianti; Bintoro Bagus Purmono; Ahmadi Ahmadi (Economic Reviews Journal, 2026)
The blind box phenomenon has developed into a popular toy trend that leverages consumers’ psychological aspects, particularly among Gen Z. This element of uncertainty not only creates surprise but also generates positive emotional responses such as curiosity, excitement, and satisfaction, which become the main attraction of blind box products. This study aims to analyze the effect of perceived uncertainty on purchase intention toward blind box products, with curiosity as a mediating variable and perceived risk as a moderating variable among Generation Z in Pontianak City, based on the Stimulus–Organism–Response (SOR) theory. This research employs a quantitative approach with a causal design, involving 200 respondents from Generation Z who are aware of and interested in purchasing blind box products, selected using purposive sampling. Data were collected through a questionnaire using a 5-point Likert scale and analyzed using PLS-SEM with the assistance of SmartPLS 4.0 software. The results indicate that perceived uncertainty has a positive and significant effect on curiosity but does not have a significant direct effect on purchase intention. Furthermore, curiosity has a positive and significant effect on purchase intention and significantly mediates the relationship between perceived uncertainty and purchase intention. Meanwhile, the moderating effect of perceived risk on the relationship between perceived uncertainty and purchase intention is not significant. This study provides theoretical contributions to the development of SOR theory in the context of uncertainty marketing in blind box products, as well as practical implications for businesses in creating more engaging experiences and managing risk to enhance purchase intention